Konsep Gharar dan Maysir dan Aplikasinya pada Lembaga Keuangan Islam - Ar Royyan Ramly (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
This paper aims to analyze and provide an understanding of the application of gharar and maysir in financial institutions. Islamic financial institutions must avoid the components of gharar and maysir in the implementation of financing and funding. Gharar is often associated with a risk or danger faced in a transaction or investment activity; we can see the component of gharar in two parts, namely gharar fahisy and gharar yasir. Maysir is often met with conditions of speculation when investing both in the capital market and money market, causing one party to feel disadvantaged. Therefore both gharar and maysir components must be avoided in the Islamic financial institutions. DOI: https://doi.org/10.5281/zenodo.3236462